Association of albumin-bilirubin grade with survival outcomes in patients with cholangiocarcinoma - Jing Ye; Rongqiang Liu; Jianguo Wang; Wangbin Ma; Chen Chen; Jia Yu; Weixing Wang (PLoS ONE, 2025)
Background Numerous studies have reported the association between preoperative albumin-bilirubin (ALBI) grade and survival outcomes in patients with cholangiocarcinoma (CCA). However, the results are inconsistent. Therefore, we conducted a meta-analysis to comprehensively evaluate the relationship between ALBI grade and prognosis of CCA patients. Methods We retrieved the databases (Pubmed,Embase and Web of science) to search articles about the association of ALBI grade with prognostic value in CCA patients. Hazard ratios (HR) and 95% confidence intervals (CI) were used to summarize survival outcomes. STATA 12.0 was used to implement the data analyses. Results 11 studies from 10 articles comprising 2841 patients were included in the meta-analysis. The pooled results showed that high ALBI grade was significantly associated with poor overall survival (OS) (HR: 1.75, 95% CI: 1.32–2.31) and relapse-free survival(RFS)(HR:1.95;95%CI:1.37–2.13). Subgroup analysis further showed that high ALBI grade had better predictive value for Asian population(HR:1.92;95%CI:1.46–2.51). Sensitivity analysis indicated that the results of the meta-analysis were stable. Conclusions High ALBI grade predicted adverse survival outcomes in CCA patients. ALBI grade may be an efficient and convenient prognostic indicator in CCA patients for Asian population.